Cash For Work Program At Nanga Pamolontian Village In Terms Of Good Enough Governance Perspective - Triadi Eka Asi Jayadiputera; Sumartono; Muhammad Nuh; Sujarwoto (Brawijaya University, 2022)
Good governance, which was originally expected to be able to solve problems in developing countries, turned out to meet many obstacles, one of which was the application of the one size fit for all pattern, which was then criticized by Grindle through the concept of Good Enough Governance (GEG). Cash For Work (CFW) Program which is one of the reform programs as an embodiment of good governance that involves community participation as labor. During its journey, the CFW encountered various problems in the field, so it was interesting to see how the CFW program was viewed from the perspective of GEG. This study aims to describe and analyze the characteristics of the arena, institutions and interests as well as actions and choices in the perspective of GEG in the implementation of CFW program in Nanga Pamolontian Village, Bulik District, Lamandau Regency, Central Kalimantan Province. This research method uses a qualitative case study approach. The results of this study are that in the implementation of CFW program they have not paid attention to the elements of GEG, both in the arena, institutions and interests and actions, this is because the agenda setting has not utilized official and unofficial channels to the fullest, related stakeholders such as the mass media and Non-Governmental Organizations, regional apparatus, local village assistants are not fully involved in the implementation of CFW, there are no technical regulations in the implementation of CFW, the Team for Facilitating the Use of Village Funds for CFW is not utilized, evaluation, guidance and supervision have not been carried out, lack of socialization and training for the team implementing activities.